Effect of Resin Infiltration and Various Etching Techniques on the Bond Strength of Sound and Demineralized Enamel - Duygu Tuncer; Zümrüt Ceren Özduman (Ankara University, 2023)
Purpose: The objective was to assess the effect of various etching techniques on the shear bond strength(SBS) of resin infiltrated sound/ demineralized enamel. Materials and methods: A total of 180 extracted human upper incisors' enamel surfaces were utilized. Half of these specimens underwent artificial demineralization, which involved exposing to an acidic buffer with a pH of 4.8(14 days). The remaining half of the specimens were kept in their original sound condition. Subsequently, both the sound/ demineralized specimens were divided into 6 groups according to the presence (I)/absence (NI) of resin infiltrant and etching methods (35% phosphoric acid (PA), 9% hydrofluoric acid (HFA), and Er,Cr:YSGG laser(L) (n=15): Following different etching procedures, an etch-and-rinse adhesive system was used, before the application of a nanohybrid composite to the enamel surfaces. Then all specimens were submitted to SBS test (MPa). three-way ANOVA and Bonferroni test were used for statistical analysis(p=0.05). Results: PA showed the highest SBS in the I groups compared with L and HFA groups, both in demineralized and sound enamel (p lt;0.05). On sound enamel, L showed higher SBS than HFA (p lt;0.05). On demineralized enamel, L showed similar values with HFA(p gt;0.05). In the NI groups, L showed similar SBS to HFA on both demineralized and sound enamel(p gt;0.05). Conclusion:Resin-infiltrated enamel can be etched by 35% phosphoric acid without jeopardize bond strength.